Effective remediation of electronic waste contaminated soil by the combination of metal immobilization and phytoremediation. Issue 3 (June 2022) - Yu, Haochen; Ma, Jing; Chen, Fu; Zhang, Qi; Wang, Yifei; Bian, Zhengfu
Abstract: In this study, laboratorial tests were conducted to evaluate the efficiency of metal immobilization and phytoremediation for remediating an actual electronic waste (e-waste) contaminated soil. Carbon black (CB) and its modified product (MCB) were used as the metal passivators to reduce the mobility and biotoxicity of soil heavy metals, while tall fescue was employed as the plant material to enhance soil microbial activity. The results show that the extractable concentrations of Cu, Pb and Zn could be reduced by 85.3%, 86.1% and 82.4%, respectively, at a MCB dosage of 5% (w/w). The removal of persistent organic pollutants [POPs, including polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), and polybrominated diphenyl ethers (PBDEs)] was highest (83.5%) in the case of 5% MCB+plant (M5-planting treatment) compared to 22.3% for the treatment without both passivator and planting. Specifically, in M5-planting treatment, the removal ratios of PAHs, PCBs and PBDEs were 82.8%, 89.3% and 75.6%, respectively. In M5-planting treatment, naphthalene, PCB-28 and BDE-28 were the most easily removed PAH, PCB and PBDE congeners, respectively, with a removal ratio of 98.5%, 98.6% and 97.5%, respectively. Contrastly, benzo[ g, h, i ]perylene, PCB-206 and BDE-209 were the most recalcitrant PAH, PCB and PBDE congeners, respectively, with the removal efficiency of 60.6%, 57.1% and 58.3%, respectively. Adding the passivators to the contaminated soil increased plant biomass, reduced metal bioavailability, raised soil dehydrogenase activity and bacterial density. MCB demonstrated better performance than CB on accelerating POPs removal and reducing the availability of heavy metals in soil. Graphical Abstract: ga1 Highlights: Immobilization and phytoremediation was jointly used for remediating co-contaminated soil. Modified nanoscale carbon black could effectively improve remediation performance. 83.5% POPs was removed by the combination of immobilization and phytoremediation.